Exercise Induces Stromal Cell–Derived Factor-1α–Mediated Release of Endothelial Progenitor Cells with Increased Vasculogenic Function. Issue 2 (February 2015) - Chang, Edwin; Paterno, Josemaria; Duscher, Dominik; Maan, Zeshaan N.; Chen, Jerry S.; Januszyk, Michael; Rodrigues, Melanie; Rennert, Robert C.; Bishop, Sarah; Whitmore, Arnetha J.; Whittam, Alexander J.; Longaker, Michael T.; et al.
Abstract : Background: Endothelial progenitor cells have been shown to traffic to and incorporate into ischemic tissues, where they participate in new blood vessel formation, a process termed vasculogenesis. Previous investigation has demonstrated that endothelial progenitor cells appear to mobilize from bone marrow to the peripheral circulation after exercise. In this study, the authors investigate potential etiologic factors driving this mobilization and investigate whether the mobilized endothelial progenitor cells are the same as those present at baseline. Methods: Healthy volunteers ( n = 5) performed a monitored 30-minute run to maintain a heart rate greater than 140 beats/min. Venous blood samples were collected before, 10 minutes after, and 24 hours after exercise. Endothelial progenitor cells were isolated and evaluated. Results: Plasma levels of stromal cell–derived factor-1α significantly increased nearly two-fold immediately after exercise, with a nearly four-fold increase in circulating endothelial progenitor cells 24 hours later. The endothelial progenitor cells isolated following exercise demonstrated increased colony formation, proliferation, differentiation, and secretion of angiogenic cytokines. Postexercise endothelial progenitor cells also exhibited a more robust response to hypoxic stimulation. Conclusions: Exercise appears to mobilize endothelial progenitor cells and augment their function by means of stromal cell–derived factor 1α–dependent signaling. The population of endothelial progenitor cells mobilized following exercise is primed for vasculogenesis with increased capacity for proliferation, differentiation, secretion of cytokines, and responsiveness to hypoxia. Given the evidence demonstrating positive regenerative effects of exercise, this may be one possible mechanism for its benefits.